Analysis of Masticatory Cycle Efficiency in Complete Denture Wearers - Goiato, Marcelo Coelho [UNESP]; Garcia, Alicio Rosalino [UNESP]; Santos, Daniela Micheline dos [UNESP]; Zuim, Paulo Renato Junqueira [UNESP] (Wiley-Blackwell, 2010)
Purpose: This study assessed masticatory efficiency and duration of the masticatory cycle in 14 asymptomatic patients with severe bone resorption. All patients had worn complete dentures for over 10 years. Recall visits were scheduled at 5 months and 1 year after receiving new dentures.Materials and Methods: Fourteen patients were evaluated in this study. The Research Diagnostic Criteria questionnaire and tests of the efficiency and duration of the masticatory cycle were performed with artificial food before, 5 months after, and 1 year after new dentures were delivered. Masticatory efficiency was assessed using a sieve system; artificial food was ground for 35 masticatory cycles and monitored by the operator.Results: Masticatory efficiency at 5 months was significantly improved for the 0.42-mm mesh. An improvement in masticatory efficiency and a reduction in mastication time were observed with the new dentures after 1 year.Conclusion: The results of this study indicated that 5 months did not allow enough time to demonstrate improved muscular capacity and ability after receiving new dentures. After 1 year, the duration of the masticatory cycle was reduced, and masticatory efficiency was significantly improved.
Keywords: Efficiency; cycles; complete dentures